Studies on Rice Bran Wax as Modified Pharmaceutical Excipient - Malviya, Rajeev (International Journal of Pharmaceutical & Biological Archive, 2017)
Waxes have been used in many cosmetic preparations and pharmaceuticals as formulation aids. Rice bran wax is a byproduct of rice bran oil industry. Present investigation has been aimed to explore the possible utility of rice bran wax as ointment base compared to standard base. In the pharmaceutical industries, waxes have been employed for different preparation, such as tablet, ointment, emulsion and even in micro-particles. So study of drug release properties using waxes is far most important. Some waxes like bees wax, carnauba wax, paraffin wax and sugarcane wax etc. are available in the market and is being used by pharmaceutical industries. Present study attempts to find if rice bran wax is useful as ointment base. The oleaginous type ointment bases is prepared by using rice bran wax and evaluated for their clarity, pH, viscosity, spread ability, skin irritation test in vitro diffusion studies and compared with the marketed formulations. The results obtained in the present study indicate, rice bran wax can be used as a good component in ointment base, comparable with white wax.